Assessment of macrovascular and microvascular function in aging males - Babcock, Matthew C; DuBose, Lyndsey E; Witten, Teresa L; Brubaker, Ashley; Stauffer, Brian L; Hildreth, Kerry L; Moreau, Kerrie L (Journal of applied physiology (1985), 2021)
Aging is associated with reductions in endothelial function, observations primarily reported using brachial artery ultrasound. There is growing interest in the use of peripheral artery tonometry (PAT) of microvessels in the fingertip to assess endothelial function because it is less technically demanding and has a high sensitivity and specificity for assessing coronary endothelial function. Moreover, similar to brachial artery flow-mediated dilation (FMD), PAT predicts cardiovascular disease outcomes. However, the relationship between PAT and FMD have yet to be examined in the context of aging. To address this question, reactive hyperemic index (RHI) using EndoPAT and FMD using brachial artery ultrasound were assessed after 5 min of forearm ischemia in 20 younger (18-40 yr old; 29 ± 4 yr) and 20 older (60-75 yr old; 65 ± 4 yr) healthy adult men. Higher values of both FMD and RHI indicate better endothelial function. Endothelial function assessed via brachial artery FMD was lower in older (4.8 ± 2.1%), compared with younger (7.5 ± 1.6%) men ( < 0.001). In contrast, the RHI assessed via PAT was greater in older (2.2 ± 0.6), compared with younger (1.8 ± 0.5) men ( = 0.014). FMD and RHI were not correlated ( = -0.15; = 0.35). We conclude that PAT may not be an appropriate measure to evaluate age-associated changes in endothelial function. Microvessel endothelial function assessed via finger plethysmography may not reflect age-associated reductions in large artery endothelial function assessed via brachial artery flow-mediated dilation.